Halal Certification of Insect-Based Food: a critique - TAJUDEEN, AHMAD LABEEB (IJIBE (International Journal of Islamic Business Ethics), 2020)
In 2013, the United Nations began to campaign for insect consumption as a rich source of high-quality protein and minerals, to thwart the predicted global food shortage and to reduce greenhouse emission. Consequently, entomophagy (or insect consumption) began to receive stronger impetus, and many food industries and investors are developing an interest in insect-based food production. With the global edible insect market estimated to reach US$1.2 billion by 2023, and the Halal industry predicted to reach US$2.6 trillion by 2023, a good understanding of the interplay between the two industries is a necessity. However, while more insects are increasingly becoming parts of processed foods globally, halal certification bodies do not hold a unified stand on the halalness of insects and their extracts, and some of the arguments raised by some Islamists lack rigorous analysis. This paper juxtaposed the views of the four Sunni Madhabs (schools of Islamic Canon law) on insect consumption and drew on the Qur’an linguistics to derive the relevant factors that must be considered when certifying insect-based gastronomic items as Halal. The novelty of this paper lies in exposing the cultural milieu that informed the verdicts of the classical scholars on insect consumption, which later became the harbinger for the controversies among the contemporary halal certification bodies. The paper seeks to pave the way for a unified Islamic stand with regards to insect consumption.     Keywords: Insect-consumption, Insect-based food, halal certification, Halalan-Tayyiban, Islamic Classical scholars.